Christian orientation programs regarding birth control in Peru - Pazos Gamio, Pedro (2015)
A responsible parenthood program located in parochial clinics of several slum areas, initiated in April 1967 and oriented within a Roman Catholic approach is described. Educational aspects receive major emphasis through a system of catholic couples, social workers and family educators. These act  giving information on moral as well as medical aspects of responsible parenthood. Oral contraceptives have been provided to 4,028 women for up to two years post-partum for child spacing.  Additionally a rhythm clinic is also in operation. Fertility data as well as dato on side effects of oral contraceptives is provided.